A Comprehensive Survey on Ensemble Learning-Based Intrusion Detection Approaches in Computer Networks - Lucas, Thiago Jose [UNESP]; De Figueiredo, Inae Soares [UNESP]; Tojeiro, Carlos Alexandre Carvalho [UNESP]; De Almeida, Alex Marino G. [UNESP]; Scherer, Rafal; Brega, Jose Remo F. [UNESP]; Papa, Joao Paulo [UNESP]; Da Costa, Kelton Augusto Pontara [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
Machine learning algorithms present a robust alternative for building Intrusion Detection Systems due to their ability to recognize attacks in computer network traffic by recognizing patterns in large amounts of data. Typically, classifiers are trained for this task. Together, ensemble learning algorithms have increased the performance of these detectors, reducing classification errors and allowing computer networks to be more protected. This research presents a comprehensive Systematic Review of the Literature where works related to intrusion detection with ensemble learning were obtained from the most relevant scientific bases. We offer 188 works, several compilations of datasets, classifiers, and ensemble algorithms, and document the experiments that stood out in their performance. A characteristic of this research is its originality. We found two surveys in the literature specifically focusing on the relationship between ensemble techniques and intrusion detection. We present for the last eight years covered by this survey a timeline-based view of the works studied to highlight evolutions and trends. The results obtained by our survey show a growing area, with excellent results in detecting attacks but with needs for improvement in pruning for choosing classifiers, which makes this work unprecedented for this context.
Keywords: Cybersecurity; ensemble learning; intrusion detection systems; machine learning